Hubungan Antara Umur, Jenis Kelamin, Indeks Massa Tubuh, Lama Latihan Dengan Daya Ledak Otot Tungkai Pada Atlet Taekwondo - Handariati, Atik; Aji Gandika, Galih (CV RIFAINSTITUT, 2021)
Taekwondo is a martial sport that relies on kicks. For a taekwondo athlete to kick, it is necessary to support the explosive power of the leg muscles. This study aims to analyze the relationship between age, sex, body mass index, length of exercise with leg muscle explosive power in taekwondo athletes. Subjects and Methods: This analytic descriptive study used a cross sectional design. The subjects of the study were taekwondo members at Sangkuriang Sports Hall and Lions Gymnasium in Cimahi City, West Java Province, totaling 95 people. The dependent variable is leg muscle explosive power. The independent variables were age, gender, body mass index and duration of exercise. The instruments used are questionnaires and vertical jump measuring instruments. Data were analyzed bivariately using OR and chi square test. The explosive power of the limbs increased with increasing age (OR= 2.89; 95% CI= 1.23 to 5.77; p= 0.010) and duration of exercise (OR= 7.44; 95% CI= 2.96 to 18.67; p <0.001). Leg explosive power decreased with body mass index but not statistically significant (OR= 0.72; 95% CI= 0.30 to 1.18; p= 0.600). Gender increased limb explosive power, but not statistically significant (OR= 1.14; 95% CI= 0.51 to 2.56; p= 0.900). The explosive power of the limbs increases with age and duration of exercise. The relationship between limb explosive power and sex and body mass index was not statistically significant